Communication skills in English part 1 - Olonan, Zenaida A.; Navarro, Paz N. ; Uyan, Lydia A. ; Villa, Emma R. (Mandaluyong City, 1982)
provides material for a semester's work for college freshmen. It aims primarilyto provide students with basic skills in the use of the language as a tool of learning and for communicative competence in business, science, and technology
Keywords: English language- study and teaching